2003
DOI: 10.1557/proc-766-e5.7
|View full text |Cite
|
Sign up to set email alerts
|

Wafer Thinning for Monolithic 3D Integration

Abstract: A three-step baseline process for thinning of bonded wafers for applications in threedimensional (3D) integration is presented. The Si substrate of top bonded wafer is uniformly thinned to ~35 μm by backside grinding and polishing, followed by wet-etching using TMAH. No visible changes at the bonding interface and damage-free interconnect structures are observed after the thinning process. Both mechanical and electrical integrity of the bonded pairs are maintained after the three-step baseline thinning process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Via chains with specific contact resistance $5 Â 10 À6 O cm 2 were demonstrated [46] by integrating wafer-to-wafer alignment, bonding, HAR etching in inductively coupled plasma (ICP), HAR filling using CVD copper, and thinning to an etch stop. This approach has demonstrated that active devices and passive copper/low-k structures can survive this bonding process and an aggressive thinning process several times over [47], thermal cycling to 400 8C [48], liquid-to-liquid thermal shock, and autoclave tests [49,50], and that the advantageous stress-buffering features of BCB remain after bonding [50].…”
Section: Wafer-level 3d Using Adhesive Bondingmentioning
confidence: 99%
See 2 more Smart Citations
“…Via chains with specific contact resistance $5 Â 10 À6 O cm 2 were demonstrated [46] by integrating wafer-to-wafer alignment, bonding, HAR etching in inductively coupled plasma (ICP), HAR filling using CVD copper, and thinning to an etch stop. This approach has demonstrated that active devices and passive copper/low-k structures can survive this bonding process and an aggressive thinning process several times over [47], thermal cycling to 400 8C [48], liquid-to-liquid thermal shock, and autoclave tests [49,50], and that the advantageous stress-buffering features of BCB remain after bonding [50].…”
Section: Wafer-level 3d Using Adhesive Bondingmentioning
confidence: 99%
“…High-throughput processes that are able to thin 200 -mm wafers to a thickness of 100 mm have been demonstrated [47,81]. Pushing this capability to a thinner final thickness results in remaining silicon thickness being dominated by removal rate nonuniformities.…”
Section: Timed Removal Thinning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these processes, the alignment and bonding are affected most by wafer scale nonplanarity, while the back side thinning step induces wafer scale nonplanarity issues which are best addressed by a three-step thinning process which stops on a buried oxide, i.e. an SOI approach [12]. During alignment and bonding, high bonding down-force and vacuum chucks are able to compensate for reasonable wafer bow and warp but the other effects must be considered as a constraint on the 3D approach employed.…”
Section: Wafer Scale Effectsmentioning
confidence: 99%
“…These bonding, thinning, and interconnection processes are repeated each time a wafer is added to the stack. 2,[13][14][15][16][17] In this paper, we discuss the impacts of wafer bonding and thinning processes on the mechanical and electrical properties of wafers. We use procedures designed to avoid both wafer-to-wafer alignment and interwafer processing to interconnect devices.…”
mentioning
confidence: 99%